UF/IFAS Standardized Nutrient Recommendations for Vegetable Crop Production in Florida: CIR1152/CV002, rev. 12/2021 - Mylavarapu, Rao; Hochmuth, George; Liu, Guodong (EDIS, 2022)
This publication presents the fertilization recommendations for vegetable crops based on soil tests performed by the UF/IFAS Extension Soil Testing Laboratory (ESTL). It contains the basic information from which ESTL soil test reports and fertilization recommendations are generated. The audiences for this information include commercial and small farmers, crop advisers and consultants, state and local agencies, fertilizer industry, and any interested individuals interested in sustainable nutrient and environmental management. Major revision by Rao Mylavarapu, George Hochmuth, and Guodong Liu; 12 pp. https://edis.ifas.ufl.edu/cv002